Temperature Estimates of Lower Miocene (Burdigalian) Coastal Water of Southern India Using a Revised Otolith “Clumped” Isotope Paleothermometer - K. Prasanna; Prosenjit Ghosh; Robert A. Eagle; Aradhna Tripati; Vivesh V. Kapur; Richard F. Feeney; Benjamin R. Fosu; Divya Mishra (Geochemistry, Geophysics, Geosystems, 2021)
Abstract Carbonate clumped isotope thermometry is based on the ordering of 13C and 18O in the carbonate lattice and is based on the relative abundance of 13C18O16O in CO2 produced through acid digestion of carbonate minerals. The major advantage of this technique is its non‐dependency on the δ18O value of water from which the carbonate precipitated. Ghosh et al. (2007, https://doi.org/10.1016/j.gca.2007.03.015) previously published calibration data for fish otoliths referenced to heated gases and used the Gonfiantini 17O parameter set in their data evaluation. Herein, we present a new clumped isotope (Δ47) calibration for aragonitic fish otoliths in the absolute reference frame using the International Union of Pure and Applied Chemistry 17O correction. Our revised calibration equation for otolith is: Δ47CDES=0.0364±0.005×(106)T2+0.2619±0.0657(R2=0.9,p−value<0.001). To test the accuracy of this calibration, we apply it to otoliths of modern Lutjanus lutjanus from the Bay of Bengal. The estimated average temperature (22.3°C ± 4.2°C) for the Bay of Bengal and δ18OV‐SMOW composition of waters of −1.7‰ (±0.5) are consistent with the onsite observations. We also apply the new calibration to well‐preserved otoliths of “genus Ambassidarum” sp. and “genus Gobiidarum” sp. from lower Miocene (Burdigalian) sediments of the Quilon Formation, India to quantify coastal water conditions. Estimated average environmental water temperatures in their habitats were 12.9°C ± 1.7°C, and the average δ18OV‐SMOW of ambient waters calculated yielded a value between −3.5‰ and −2.6‰ (V‐SMOW) (mean: −2.9‰ ± 0.4) and −4.4‰, respectively. These results indicate δ18O values reflect the kinetic effects impacting the δ18O of fish otoliths independently of Δ47, although we cannot fully preclude diagenesis.